Geochemistry, zircon U-Pb geochronology and Sr-Nd-Hf isotopic composition of the Cha Val plutonic rocks in central Vietnam: Implications for Permian-Triassic Paleo-Tethys subduction-related magmatism - Pham, Minh; Pham Trung, Hieu; Kawaguchi, Kenta; Nong Thi Quynh, Anh; Le Duc, Phuc (Vietnam Journal of Earth Sciences, 2021)
The Cha Val plutonic rocks emplaced in the south of the Truong Son belt (north of Kontum massif, Central Vietnam) together with abundant Permian-Triassic magmatic rocks. This magmatic complex provides important information to reconstruct the tectonic evolution of the Indochina block and surrounding areas. The Cha Val plutonic rocks mainly comprise diorite, quartz diorite, and granodiorite. Geochemically, they are metaluminous with low A/CNK (0.49 to 1.16 with an average of 0.85), medium to high K, low to medium SiO2, and Na2O/K2O>1. Trace and rare earth element compositions display enrichment in Cs, U, Pb, and Nd, but depletion in Ba, Nb, Ta, P, Eu, and Ti, similar to those of continental arc-related magmas. Rock-forming minerals of the Cha Val plutonic rocks are characterized by abundant hornblende. All observed petrographical and geochemical characteristics suggest that the Cha Val plutonic rocks are typical for I-type affinity generated from a subduction regime. LA-ICP-MS U-Pb zircon analyses of three representative samples yielded their crystallization ages between 258.0 Ma and 248.9 Ma, temporally coeval with Late Permian-Early Triassic magmatism previously reported in the Truong Son belt. The (87Sr/86Sr)i ratios (0.7081 to 0.7244), negative whole-rock εNd(t) values (-4.5 to -2.9), zircon εHf(t) values (-1.04 to 2.71), and whole-rock Nd and zircon Hf model ages (TDM2) (1394 Ma to 1111 Ma) indicate that the Cha Val plutonic rocks are derived from melting of Mesoproterozoic crustal materials with a minor contribution of mantle-derived melt. Together with other Permian-Triassic magmatic complexes along the Song Ma suture zone and the Truong Son Belt, the Cha Val plutonic rocks are a representative of magmatism associated with the subduction-collision that amalgamated the South China and Indochina blocks after the closure of a branch of Paleo-Tethys along the Song Ma suture zone during the Late Permian-Early Triassic Indosinian orogeny.